English Language Acquisition through Parliamentary Debating: A Case Study at Politeknik Kesehatan Mataram - Suhendra, Erwin; Syarifaturrahman, Wahyu Kamil; Darmajaya, Lalu Arwan (LPPM Universitas Bumigora Mataram, 2025)
British Parliamentary (BP) debate is widely adopted in EFL/ESP classrooms, but prior studies often report score gains without explaining how debate drives language development. This study aimed to trace the mechanisms by which BP debate fosters L2 acquisition, focusing on fluency, discourse organisation, and pragmatic competence. Using a qualitative research method with process tracing, eight medical ESP students at Politeknik Kesehatan Mataram completed four full BP rounds. Multimodal data included audio–video recordings of speeches and POIs, written texts from case building, observational notes, and reflective journals/interviews. Data were transcribed and analysed through reflexive thematic analysis guided by three constructs: noticing, modified output, and mediation. Results show a consistent input–processing–output–mediation cycle: self-repairs declined while lexical precision increased; signposting and connectors became denser and more strategic; POIs/rebuttals featured clearer negotiation through hedging, uptake, and reformulation; and adjudicator feedback catalysed planned changes in subsequent rounds, indicating developing self-regulation. Overall, BP debate functions as a rich, mechanism-rich environment that integrates sociocultural mediation with interactionist learning, transforming performance from mechanical repetition to purposeful, confident communication. These findings support using BP debate as an authentic task-based pedagogy for ESP learners.